German-speaking archaeology is more - Meier, Thomas (Archaeological dialogues, 2017)
In a way - as the authors admit themselves - Kerstin Hofmann's and Philipp Stockhammer's paper is very German. Most of their paper reads like a long catalogue, collecting and arranging as many recent GSA contributions to anglophone debates as the authors could find. In the end their catalogue sums up to the impressive number of around four hundred references.